Respuesta :
Multiply −6 by 9 to get −54.(5−54+6)⋅9+3−85Subtract 54 from 5 to get −49.(−49+6)⋅9+3−85Add −49 and 6 to get −43.−43⋅9+3−85Multiply −43 by 9 to get −387.−387+3−85
Add −387 and 3 to get −384.−384−85Subtract 85 from −384 to get −469.−469
thats what i did to get -469. show your work for finding -109 and we can compare
Add −387 and 3 to get −384.−384−85Subtract 85 from −384 to get −469.−469
thats what i did to get -469. show your work for finding -109 and we can compare
So we have
(5-6x9+6)x9+3-85
So this is a oder of operation question, firstly you start with the brackets
(5-6x9+6)
B. Brackets
E. Exponents
D. Division
M. Multiplication
A. Addition
S. Subtraction
(5-6x9+6)
Multiplication first
6x9=54
Now we have
(5-56+6)
56+6=62
62-5=57
((57))
Now we have left
57x9+3-85
Start from multiplication
57x9=513
513+3= 516
516-85= 413
413
(5-6x9+6)x9+3-85
So this is a oder of operation question, firstly you start with the brackets
(5-6x9+6)
B. Brackets
E. Exponents
D. Division
M. Multiplication
A. Addition
S. Subtraction
(5-6x9+6)
Multiplication first
6x9=54
Now we have
(5-56+6)
56+6=62
62-5=57
((57))
Now we have left
57x9+3-85
Start from multiplication
57x9=513
513+3= 516
516-85= 413
413